APPLICATIONOF BLUE COLOR THERAPY TO REDUCING STRESS LEVELS IN THE ELDERLY IN THE AREA PUSKESMAS ROWOSARI SEMARANG - Muhammad Wisnu Prayoga; Margiyati, Ns. Margiyati (International Journal Of Health Science, 2021)
Decreased physical abilities, the emergence of disease, and psychosocial changes are sources of stress in the elderly ehich can develop into depression and even suicide. Treatment with anti-depresant in the long run cause dangnerous side effects. Blue color therapy is a safe complementary therapy using electromagnetic radiation spectrum which produces a relaxing effect and reducing stress in the elderly This therapy is one of the non pharmacological therapies that can reduce stress levels in the elderly in the area of puskesmas rowosari semarang.the type of research used is descriptive method of case study approach. The subject used by 2 people with the criteria of being willing to be an opponent, no suffer from color blindness, elderly with mild to moderate stress levels, elderly who like the blue color. Measurement of stress levels using depresion anxiety stress scale (DASS42), interventions of blue color therapy for 7 consecutive days, the results of the analysis obtained by subject 1 decreased from 20 (moderate stress) to 14 (mild stress), subject II from 22 (moderate stress) to 16 (moderate stress). The result of the case studies concluded that there was a reduction in stress levels reaching 6 score DASS42. The application of blue color therapy is recomended as a nursing intervention in the management of reduced stress levels in the elderly.the application of blue therapy is effective in reducing stress in the elderly, so it is recomended as a nursing intervention in the management of reducing stress levels in the elderly